Implementasi Gamifikasi dalam E-commerce: Mengungkap Upaya Peningkatan Brand Love melalui Customer Engagement yang Dimoderasi Immersion - Kennu Simarmata; Yolanda Masnita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research was conducted to analyze the influence of Gamifaction elements such as Challenges, Points, Enjoyment, Badges on Brand love which is mediated by Customer Engagement and moderated by Immersion on Gamifaction users in e-commerce. This research refers to research conducted by (Tsou & Putra, 2023). In this research, the research design used is quantitative research. The data analysis method used in this research is the Partial Least Square method based on Structural Equation Modeling. Research data was taken by means of Cross Sectional Studies, because the data was collected within a predetermined time period and period, by conducting survey research by distributing questionnaires with Google Forms to Gamifaction users on e-commerce and the data was processed using Smart PLS versi 4.0 software. The results show that all Gamifaction elements (Challenges, Points, Enjoyment) except Badges have been proven to be factors that directly influence Customer engagement and Customer engagement has been proven to be a factor that directly influences Brand love. Apart from that, Customer engagement has also been proven to mediate an indirect relationship between all Gamifaction elements (Challenges, Points, Enjoyment) except Badges towards Brand love and Immersion has been proven to mediate an indirect relationship between Customer engagement towards Brand love.